The Effect of Lifestyle on Social and Social Norm: A Case Study of Male University Students at a Public University in Banten, Indonesia - Lenny Wahyuningsih; Putri Dian Dia Conia; Meilla Dwi Nurmala; Aisling O’Boyle; Siti Muhibah; Bangun Yoga Wibowo (Jurnal Pendidikan Indonesia Gemilang, 2023)
Developments in technology and culture affect a person's attitude and lifestyle. Lifestyle describes the "whole person" who interacts with his environment. One of the trendy lifestyles in demand by various people, including students, is the modern lifestyle. Modern lifestyles influence consumers' consumption decisions because good images will arise if we can follow this lifestyle. Especially in social problems, where to hang out, and style in appearance. So, a person's lifestyle is related to his association and social norms that are carried out in the surrounding environment. This study aimed to determine the relationship between the influence of lifestyle on student association and social norms. This research uses a quantitative approach with a correlational study. Respondents in this study were male students at a state university in Banten, Indonesia, which consisted of the Faculty of Law, Faculty of Medicine, Faculty of Teaching and Education, Faculty of Engineering, Faculty of Business Economics, Faculty of Agriculture, Faculty of Social and Political Sciences, totaling 115 people. Data collection uses a VALS scale questionnaire (adaptation). The results of this study indicate that there is an influence of lifestyle on association and social norms. A simple lifestyle following the circumstances of the respondents influences associations that do not require a "brand image" or require branded goods in their association. As well as influences social norms as well. If lifestyle changes, then the behavior shown will also affect the social norms that it does.